The Synthesis of Edible Film from Tilapia Fish (Oreochromis niloticus) Bones for Ecofriendly Material of Halal Packaging Applications - Windayani, Neneng; Irwansyah, Ferli Septi; Effendi, Meila N (UIN Sunan Gunung Djati Bandung, 2020)
Packaging materials, especially in food is the most important of healthy aspect. However, today many types of packaging materials used are hazardous to health and environment, then was found alternative halal packaging materials that are safe for health and environment. One of the alternatives is edible film, synthesis from tilapia bone gelatin, it is using sorbitol as plasticizer. Edible film synthesized by dissolving tilapia fish (Oreochromis niloticus) from bone gelatin in distilled water containing sorbitol, then stirred, poured on flat glass, and heated at 50°C. The procedure is performed with a concentration of gelatin (8% and 10% w/v) and sorbitol (25% and 37% v/v). Then was characterized it is mechanical properties include thickness, tensile strength, and elongation to determine eligibility. The optimum condition of the edible film was obtained from 10% concentration of gelatin with 37% sorbitol, with the character of it is mechanical properties value are 0.05 mm thickness, 3,07 MPa tensile strength, and 64.34% elongation.